A catalogue of Bombycoidea of India (Lepidoptera) - Irungbam, Jatishwor Singh; Kalawate, Aparna; Ahmad, Jalil; Bhattacharya, Kamalika; Joshi, Rahul; Singh, Navneet (Zootaxa, 2026)
Herein, we catalogue 404 species in 115 genera and six families of Bombycoidea from India i.e., Bombycidae (25 species in 11 genera), Brahmaeidae (2 species in single genus), Endromidae (11 species in seven genera), Eupterotidae (53 species in 15 genera), Saturniidae (78 species in 16 genera) and Sphingidae (235 species in 65 genera). Sphingidae exibit the highest diversity, whereas Brahmaeidae represent the lowest diversity in India. Anthelidae, Apatelodidae, Carthaeidae and Phiditiidae are not reported from India. For all included families, information about adult and larval morphology, as well as the diversity and distribution of subfamilies present in India, is provided. For each genus, the type species and synonymy are provided whereas, for each species, the type locality, synonymy, distribution within India, and global distribution are provided.